Microglial Over-Activation by Social Defeat Stress Contributes to Anxiety- and Depressive-Like Behaviors - Stein, Dirson J.; Vasconcelos, Mailton F.; Albrechet-Souza, Lucas; Ceresér, Keila M. M.; de Almeida, Rosa M. M. (Frontiers in Behavioral Neuroscience, 2017)
Hyper activation of the neuroimmune system is strongly related to the development of neuropsychiatric disorders. Psychosocial stress has been postulated to play an important role in triggering anxiety and major depression. In preclinical models, there is mounting evidence that social defeat stress activates microglial cells in the central nervous system. This type of stress could be one of the major factors in the development of these psychopathologies. Here, we reviewed the most recent literature on social defeat and the associated immunological reactions. We focused our attention on microglial cells and kept the effect of social defeat over microglia separate from the effect of this stressor on other immune cells and the influence of peripheral immune components in priming central immune reactions. Furthermore, we considered how social defeat stress affects microglial cells and the consequent development of anxiety- and depressive-like states in preclinical studies. We highlighted evidence for the negative impact of the over-activation of the neuroimmune system, especially by the overproduction of pro-inflammatory mediators and cytotoxins. Overproduction of these molecules may cause cellular damage and loss or decreased function of neuronal activity by excessively pruning synaptic connections that ultimately contribute to the development of anxiety- and depressive-like states.